Impaired mitochondrial function is abrogated by dexrazoxane in doxorubicin‐treated childhood acute lymphoblastic leukemia survivors. Issue 6 (13th January 2016) - Lipshultz, Steven E.; Anderson, Lynn M.; Miller, Tracie L.; Gerschenson, Mariana; Stevenson, Kristen E.; Neuberg, Donna S.; Franco, Vivian I.; LiButti, Daniel E.; Silverman, Lewis B.; Vrooman, Lynda M.; Sallan, Stephen E.
Abstract : BACKGROUND: Impaired cardiac function in doxorubicin‐treated childhood cancer survivors is partly mediated by the disruption of mitochondrial energy production. Doxorubicin intercalates into mitochondrial DNA (mtDNA) and disrupts genes encoding for polypeptides that make adenosine triphosphate. METHODS: This cross‐sectional study examined mtDNA copy numbers per cell and oxidative phosphorylation (OXPHOS) in peripheral blood mononuclear cells (PBMCs) in 64 childhood survivors of high‐risk acute lymphoblastic leukemia (ALL) who had been treated on Dana‐Farber Cancer Institute childhood ALL protocols and had received doxorubicin alone (42%) or doxorubicin with the cardioprotectant dexrazoxane (58%). The number of mtDNA copies per cell and the OXPHOS enzyme activity of nicotinamide adenine dinucleotide dehydrogenase (complex I [CI]) and cytochrome c oxidase (complex IV [CIV]) were measured with quantitative real‐time polymerase chain reaction immunoassays and thin‐layer chromatography, respectively. RESULTS: At a median follow‐up of 7.8 years after treatment, the median number of mtDNA copies per cell for patients treated with doxorubicin alone (1106.3) was significantly higher than the median number for those who had also received dexrazoxane (310.5; P  = .001). No significant differences were detected between the groups for CI or CIV activity. CONCLUSIONS: Doxorubicin‐treated survivors had an increased number of PBMC mtDNA copies per cell, and concomitant use of dexrazoxane was associated with a lower number of mtDNA copies per cell. Because of a possible compensatory increase in mtDNA copies per cell to maintain mitochondrial function in the setting of mitochondrial dysfunction, overall OXPHOS activity was not different between the groups. The long‐term sustainability of this compensatory response in these survivors at risk for cardiac dysfunction over their lifespan is concerning. Cancer 2016;122:946–53 . © 2016 American Cancer Society . Abstract : Impaired cardiac function in doxorubicin‐treated childhood cancer survivors is partly mediated by the disruption of mitochondrial energy production. This study provides evidence supporting the idea that dexrazoxane adjuvant therapy in pediatric patients with high‐risk acute lymphoblastic leukemia offers systemic mitochondrial protection as observed in peripheral blood mononuclear cells 7 years after treatment.